Evaluation of Home Care Program Implementation in Primary Health Care at Tobadak Public Health Center - Asmiana Saputri Ilyas; Andi Kasmawati; Andi Cudai Nur; Nurussyariah (Cendekiawan Indonesia Timur, 2025)
The home care program is a public health policy initiative designed to improve access to and the quality of primary health care services at the community health center level. This study aims to evaluate the implementation of the home care program in terms of input, process, and output aspects at the Tobadak Public Health Center, Mamuju Tengah Regency. This study employed a descriptive qualitative approach, with data collected through in-depth interviews, field observations, and document analysis. The findings indicate that, in the input aspect, facilities, infrastructure, and program funding are relatively adequate; however, human resource capacity, particularly the number of health workers and task distribution, remains suboptimal. In the process aspect, home care services have generally been implemented in accordance with established procedures, although challenges related to scheduling and coordination among implementers persist. In terms of output, the home care program provides tangible benefits for the community by improving access to health services and increasing user satisfaction. Therefore, the implementation of the home care program is considered effective; however, strengthening human resource management and public service governance is necessary to ensure more optimal and sustainable policy implementation.